Ubeydu'llah han: salavat-name ve gayret-name - Talip Yildirm, Dr. (Кримський науковий центр НАН України і МОН України, 2005)
In this article, the book of Ubeydullah Khan who was Sultans of the Ozbek's titled Salavat-name and Gayret-name are studied philologcally which has not been examined.